Pengaruh Ketebalan Material Terhadap Shielding Effectiveness pada Frekuensi Rendah - Mohammad Yanuar Hariyawan; Rizadi Sasmita Darwis; Siska Novita Posma (Politeknik Caltex Riau, 2021)
Today, the need for electronic devices with smaller and more compact dimensions integrating many functions is increasing. At the same time, the need for ubiquitous processor speed, clock, data rate, and wireless connectivity is also increasing. This increase in demand also results in an increase in electromagnetic interference (EMI) in the environment. Although rare, High-Impact, Low-Frequency (HILF) events have the potential to have a deleterious impact on the electric power system. In this study, an analysis of shielding effectiveness (SE) was carried out at low frequencies when the thickness of the shielding material was varied. The materials used in this research are aluminum sheet and aluminum foil, and they combine their thickness through a single layer or double layer scheme. The thickness of the shielding material affects the value of shielding effectiveness; as evidenced when the thickness of the material is increased to 2 times, an increase in the value of shielding effectiveness reaches 207%. The use of double layers shows an increase in shielding effectiveness which is better than increasing the thickness of the material.